Examining Empowering Leadership’s Impact on Trust and Employee Voice Behavior: A PLS SEM Model Analysis - Nizam, Kehkashan; Hameed , Samiya (Pakistan Journal of Humanities and Social Sciences, 2023)
The purpose of the study is to determine the influence of supportive leadership, voice behavior of supervisor on voice behavior of employees on in Pharmaceutical industry of Pakistan. Moreover, second objective of this study is to determine the role of trust in supervisor as a mediator between supportive leadership, voice behavior of supervisor and voice behavior of employee. The data was collected through survey questionnaire by spreading among employees working at pharmaceutical companies in Karachi, Pakistan. Total 180 sample data was analyzed and that delivered statistical results of developed hypotheses by observing previous studies. SPSS and PLS-SEM, statistical technique will use to test the hypotheses. The result found that supportive leadership and perceived voice behavior has positive affect on employee voice behavior. Further, supportive leadership has positive impact on employee voice behavior. In addition, trust in supervision positively mediates the relationship between perceived voice behavior of supervisor, supportive leadership and employee voice behavior.